Archaeological footwear : development of shoe patterns and styles from prehistory till the 1600's - Volken, Marquita ([Zwolle] : SPA Uitgevers, 2014)
"A catalogue presents each named shoe style along with the cutting patterns used, a concise description and a full list of the published examples. The volume also includes a short history of calceological studies, case studies, the fundamental research methods and an overview of shoe sole/upper constructions for archaeological leather shoes"--Publisher's website.
"This volume is the cumulation of a thesis presented at the University of Lausanne, October 2012"--Page xi.
Includes bibliographical references and index.
Text in English with summary in English, French and German.
Keywords: Antiken; Forntiden; Medeltiden; Archaeology; Archäologie; Arkeologi; Schuh; Shoes -- Design; Shoes -- History; Skor -- Framställning, tillverkning etc -- Historia; Skor -- Historia